Preparation of PLGA Nanoparticles by Milling Spongelike PLGA Microspheres - Jimin Lee; Hongkee Sah (MDPI AG, 2022)
Currently, emulsification-templated nanoencapsulation techniques (e.g., nanoprecipitation) have been most frequently used to prepare poly-d,l-lactide-co-glycolide (PLGA) nanoparticles. This study aimed to explore a new top-down process to produce PLGA nanoparticles. The fundamental strategy was to prepare spongelike PLGA microspheres with a highly porous texture and then crush them into submicron-sized particles via wet milling. Therefore, an ethyl formate-based ammonolysis method was developed to encapsulate progesterone into porous PLGA microspheres. Compared to a conventional solvent evaporation process, the ammonolysis technique helped reduce the tendency of drug crystallization and improved drug encapsulation efficiency accordingly (solvent evaporation, 27.6 ± 4.6%; ammonolysis, 65.1 ± 1.7%). Wet milling was performed on the highly porous microspheres with a D50 of 64.8 μm under various milling conditions. The size of the grinding medium was the most crucial factor for our wet milling. Milling using smaller zirconium oxide beads (0.3~1 mm) was simply ineffective. However, when larger beads with diameters of 3 and 5 mm were used, our porous microspheres were ground into submicron-sized particles. The quality of the resultant PLGA nanoparticles was demonstrated by size distribution measurement and field emission scanning electron microscopy. The present top-down process that contrasts with conventional bottom-up approaches might find application in manufacturing drug-loaded PLGA nanoparticles.